Usulan Metode Target Costing dengan Value Engineering dalam Upaya Penetapan Harga Jual Optimal Produk Frozen Food - Putri, Sabela Ardelia; Prima, Febri; Budiman, Riadi; Uslianti, Silvia; Putri, Famelga Clea (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ operates in the culinary industry with Bakso Frozen BTS as its flagship product. The selling price of IDR 149,000 per kg is considered too high, reducing competitiveness, especially in lower purchasing power markets. This issue stems from high production costs due to expensive raw materials and the lack of supplier partnerships, while consumers compare prices with cheaper competitors. This study aims to recommend an optimal selling price through target costing and identify cost efficiencies using value engineering, supported by FAST Diagram, Mudge Diagram, and Resource Consumption Matrix. Findings indicate the selling price can be reduced to IDR 139,000 to remain competitive, with the profit margin rising from 30% to 32.2%. Production costs decreased from IDR 104,300 to IDR 94,279 per pack, yielding efficiency of IDR 10,021 or 9.6% through improvements in raw materials. This method enables the company to set a more competitive price without compromising product quality.